2020
DOI: 10.1080/20008198.2020.1736411
|View full text |Cite
|
Sign up to set email alerts
|

Associations between moral injury, PTSD clusters, and depression among Israeli veterans: a network approach

Abstract: Background: Moral Injury (MI) is one of the adverse consequences of combat. Following exposure to potentially morally injurious events (PMIEs)--events perceived as violations of deep moral beliefs by oneself or trusted individuals--a significant minority of veterans could develop posttraumatic stress disorder (PTSD) and depression. Objective: The current study represents the first attempt to apply a network analysis model to examine an exploratory empirical conceptualization of a network of PMIEs during milita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 69 publications
5
35
0
Order By: Relevance
“…Instead, our results suggest these symptoms represent a downstream outcome of PTSD, which may be addressed through treating features bridging between posttraumatic stress and internalizing concerns. Consistent with our exploratory analysis of potential mechanisms, a study of Israeli veterans suggested centrality of the DSM-V NACM symptom cluster in bridging among PTSD, depressive symptoms, and moral injury (25).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Instead, our results suggest these symptoms represent a downstream outcome of PTSD, which may be addressed through treating features bridging between posttraumatic stress and internalizing concerns. Consistent with our exploratory analysis of potential mechanisms, a study of Israeli veterans suggested centrality of the DSM-V NACM symptom cluster in bridging among PTSD, depressive symptoms, and moral injury (25).…”
Section: Discussionsupporting
confidence: 79%
“…Instead, our results suggest these symptoms represent a downstream outcome of PTSD, which may be addressed through treating features bridging between posttraumatic stress and internalizing concerns. Consistent with our exploratory analysis of potential mechanisms, a study of Israeli veterans suggested centrality of the DSM-V NACM symptom cluster in bridging among PTSD, depressive symptoms, and moral injury (25). Similarly, consistent with our findings on the centrality of hyperarousal across PTSD and depressive symptom groups, other research suggests anxiety sensitivity and avoidance of inner experiences broadly may be transdiagnostic processes underlying PTSD and internalizing symptomatology (32,68,69).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Research indicates that MI is also common among the active duty armed forces of other countries as well (Battaglia et al, 2019 ; Ferrajão & Aragão Oliveira, 2016 ; Levi-Belz et al, 2020 ; Williamson et al, 2021 ). For example, Hodgson et al ( 2021 ) note the high prevalence of potentially morally injurious events (PMIEs) in a qualitative study of ten Australian Veterans, identifying seven common themes giving rise to MI symptoms: immoral acts (witnessed and perpetrated), death and injury (witnessed and perpetrated), betrayal (by others and self), ethical dilemmas (humanization/dehumanization and decision-making), disproportionate violence, retribution, and religious/spiritual issues.…”
Section: Measurementmentioning
confidence: 99%
“…The most studied link that has been found is with posttraumatic stress disorder (PTSD; Koenig, Youssef, & Pearce, 2019). Other studies have also documented direct associations with depressive symptoms (Levi-Belz, Greene, & Zerach, 2020), and destructive behaviours such as substance abuse (Currier et al, 2015) and suicidality (Bryan, Bryan, Morrow, Etienne, & Ray-Sannerud, 2014). Indeed, a recent review (Griffin et al, 2019) and a metaanalysis (Williamson, Stevelink, & Greenberg, 2018) found consistent associations between a PMIE and mental health outcomes such as PTSD, depression and suicidality, as well as other negative religious/spiritual sequelae.…”
Section: Introductionmentioning
confidence: 99%